Burnout Among Private Security Staff in Serbia: A Multicentic Cross-Sectional Study - Veljković, Dejan R.; Rancic, Natasa K.; Mirković, Momčilo R.; Kulić, Ljiljana M.; Stanković, Veroslava V.; Stefanović, Ljubomir S.; Stojanović, Marko M.; Mirković, Miloš V.; Ðurić, Slađana M.; Ilić, Danijela Z. (Frontiers in Public Health, 2021)
Background: Burnout is a special a state of physical or emotional exhaustion that also involves a sense of reduced accomplishment and loss of personal identity. Objectives: To evaluate the predictors of burnout among work staff in the seven private agencies for support and defense of persons and their property. Material and Method: We performed a multicentric cross-sectional study that involved representative sample of working staff from Agencies of Private Security in Central Serbia. Burnout was assessed using Maslach Burnout Inventory- (MBI)-Human Services Survey. Results: A total number of participants were 353 (330 men and 23 women). Measured level of burnout as assessed by high emotional exhaustion, high depersonalization, and low personal accomplishment was 66.3, 82.4, and 13.4%, respectively. We identified that female gender, younger age, shorter work experience, working in shifts, working 12 h a day and more than 8–12 h a day as well as dissatisfaction with working conditions. Work in shifts, working 12 h a day and more than 8–12 h a day and dissatisfied with dissatisfaction with working conditions significantly increase the risk of total burnout. Conclusion: Our results showed that significant predictors for the development of burnout syndrome were female gender, younger age, shorter work experience, working in shifts, as well as dissatisfaction with working conditions.